Love of life in Bharatiar Poetry - R, Sathish Kumar; S, Saraswathy (Indian Journal of Tamil, 2024)
Bharathiyar is known as Mahakavi in the world of poetry. He fought for the country and its people. He has expressed many ideas for the unity and liberation of the people through his works. Such ideas are also based on nature. Plants, birds and animals play a major role in protecting nature. People need to understand the nature of these creatures. In order to make the present day people also understand, Bharathiyar has indicated the virtues and virtues of living beings through his poems. His poems like Pappa Pattu, Kannan Pattu and Kuyil Pattu feature birds like sparrow, crow, hen and cuckoo. Bharathiyar has pointed out the special characteristics of birds by linking them with the characteristics of the people. This article explains what Bharathiyar said from the point of view of preserving them.